Fragment-based virtual screening identifies novel leads against Plasmepsin IX (PlmIX) of Plasmodium falciparum: Homology modeling, molecular docking, and simulation approaches - Almuqdadi, Haider Thaer Abdulhameed; Kifayat, Sumaiya; Anwer, Razique; Alrehaili, Jihad; Abid, Mohammad (Frontiers in Pharmacology, 2024)
Despite continuous efforts to develop safer and efficient medications, malaria remains a major threat posing great challenges for new drug discovery. The emerging drug resistance, increased toxicities, along with impoverished pharmacokinetic profiles exhibited by conventional drugs have hindered the search for new entities. Plasmepsins, a group of Plasmodium-specific, aspartic acid protease enzymes, involved in many key aspects of parasite biology makes them interesting targets for antimalarial chemotherapy. Among different isoforms (PlmI-X), PlmIX serves as an unexplored antimalarial drug target which plays a crucial role along with PlmV and X in the parasite's survival by digesting hemoglobin in the host's erythrocytes. In this study, fragment-based virtual screening was performed by modeling the three-dimensional structure of PlmIX and predicting its ligand-binding pocket by using the Sitemap tool. The screening identified the fragments with XP docking score ≤ -3kcal/mol from the OTAVA general fragment library (≈16397 fragments) and the selected fragments were chosen for ligands breeding. The resulting ligands (≈69858 ligands) were subsequently subjected to filtering based on the Qikprop properties along with carcinogenicity testing performed using Carcinopred-EL and then docked in the SP (≈14078 ligands) as well as XP mode (≈3104 ligands) and compared with that of control ligands-49C and I0L. The top-ranked ligands were taken further for the calculation of free energy of binding using the Prime MM-GBSA. Overall, a total of six complexes were taken further for MD simulation studies performed at 100ns to attain a better understanding of the binding mechanisms and compounds 3 and 4 were found to be the most efficient ones in silico. The analysis for compound 3 revealed that the carbonyl group present on position 1 on isoindoline moiety (Arg554) was responsible for inhibitory activity against PlmIX. However, the analysis for compound 4 revealed that the amide linkage sandwiched between phenyl ring and isoquinoline moiety (Lys555 and Ser226) as well as the carbonyl oxygen of carbamoyl group present at position 2 of pyrazole ring (Gln222) were responsible for PlmIX inhibitory activity, owing to their crucial interactions with key amino acid residues.